The Use of Slang among Teenagers in Interactions on Instagram Social Media: A Semantic Analysis - Madani, Nurul Firah; Hafisya, Siti Rahma; Halik, Abdul (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study explores the phenomenon of slang language use among teenagers in social interactions on Instagram, using a semantic analysis approach. The aim of the research is to identify forms of semantic meaning changes and to understand the social and linguistic functions of slang within digital communication contexts. The research employed a qualitative descriptive method with data collected through observation, documentation, and semantic theory-based analysis. The findings reveal that teenagers’ use of slang reflects dynamic changes in meaning, such as meaning broadening, narrowing, and shifting. Additionally, slang serves as a tool for shaping social identity, group solidarity, and expressing youth popular culture. The study concludes that slang represents a form of linguistic creativity influenced by cultural contexts and digital media environments.